Peran Kepemimpinan Kristen: Menelaah Kegagalan Para Hakim dan Dampaknya terhadap Israel - Fatimatul labibah; Rosita Dwi Hapsari (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2024)
The purpose of this article is to understand the context and role of Christian leadership today. Examining the failure of the judges sent by God to the nation of Israel can be a new guide for exploring in depth the important role of the presence of a leader among the faithful. The research method used is a qualitative research method with a literature review approach which can support the research above. In this case, it is hoped that the research results will provide insight into how a Christian leads. Part of the scope of this study is how to understand biblical content that can provide a literal and even allegorical interpretation of leadership ethics.